2012
DOI: 10.1128/aem.06215-11
|View full text |Cite
|
Sign up to set email alerts
|

New Betaproteobacterial Rhizobium Strains Able To Efficiently Nodulate Parapiptadenia rigida (Benth.) Brenan

Abstract: c Among the leguminous trees native to Uruguay, Parapiptadenia rigida (Angico), a Mimosoideae legume, is one of the most promising species for agroforestry. Like many other legumes, it is able to establish symbiotic associations with rhizobia and belongs to the group known as nitrogen-fixing trees, which are major components of agroforestry systems. Information about rhizobial symbionts for this genus is scarce, and thus, the aim of this work was to identify and characterize rhizobia associated with P. rigida.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
74
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 38 publications
(45 reference statements)
4
74
0
Order By: Relevance
“…Amplification of an intragenic nodA gene fragment using a NodAforB and NodArevB primer set can exhibit positive results, with sizes ranging from 245 to 800 bp (Klonowska et al, 2012;Taulé et al, 2012). So, the amplification of different molecular size amplicons found in the present study can be considered positive for both bacteria, indicating that ESA 71 exhibits a nodA gene copy with some similarity to that found in the Paraburkholderia.…”
Section: Discussionmentioning
confidence: 70%
“…Amplification of an intragenic nodA gene fragment using a NodAforB and NodArevB primer set can exhibit positive results, with sizes ranging from 245 to 800 bp (Klonowska et al, 2012;Taulé et al, 2012). So, the amplification of different molecular size amplicons found in the present study can be considered positive for both bacteria, indicating that ESA 71 exhibits a nodA gene copy with some similarity to that found in the Paraburkholderia.…”
Section: Discussionmentioning
confidence: 70%
“…Reference strains were the highly resistant bacterium Cupriavidus metallidurans CH34 (49,50), the type strains C. taiwanensis LMG19424 T (15) and B. phymatum STM815 T , the P. rigida symbionts C. necator UYPR2.512 and Burkholderia sp. UY1.413 (30), and the metalsensitive strain Escherichia coli S17-1 (51).…”
Section: Methodsmentioning
confidence: 99%
“…All of the symbiotic Cupriavidus strains described so far, as well as the isolates from the present study fall within clade I, in which three distinct subclades were also observed. Clade Ia comprises sequences from isolates UYMM14A, UYMS13B, UYMAM01A, UYMAM01B, and UYMS01A from the present study, two nodulating C. necator strains isolated from trap plants nodulated in pasture soils from Minas Gerais state in central Brazil (UFLA02-71 and UFLA01-669) (56), and strains (UYP2.512, UYPR2.54, and UYPR2.56) isolated from P. rigida nodules in Uruguay (30). Clade Ib comprises sequences of type strains of both the symbiotic species C. taiwanensis (15), as well as various unclassified Cupriavidus symbionts isolated from diverse Mimosa spp.…”
Section: Nodulation Of Nativementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have hypothesized the horizontal transfer of symbiotic genes between Alpha-and Beta-rhizobia, or between Burkholderia and Cupriavidus on the basis of phylogenies using sequences of their symbiosis-related genes, such as nodA, nodC and nifH [19,20,30,32,57] but both vertical and horizontal transfer occur in Burkholderia [13] their phylogenies displaying signs of the origin of Beta-rhizobia to some degree. Although it is widely reported [58], some reports have indicated that horizontal gene transfer (HGT) has not been common even within Alpharhizobia, as revealed by the nodA and nodC phylogenies of some Ensifer and Rhizobium symbionts [8,31].…”
mentioning
confidence: 99%